Development of physical education teacher attitude instruments towards stimulating HOTS: PE-SHOTS questionnaire - Hardiansyah, Sefri; Zalindro, Ade (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2025)
Students need higher-order thinking skills (HOTS) to develop optimally and answer the challenges of the 21st century. In addition, HOTS also needs stimulation in the learning process to grow optimally, and the teacher's decision to stimulate HOTS is highly dependent on the teacher's attitude towards stimulating HOTS itself. Hence, the teacher's attitude towards stimulating HOTS must be revealed. However, until now, teachers' attitudes, especially in physical education, towards stimulating HOTS have not been identified with certainty due to the unavailability of valid and reliable instruments. This study aims to develop an instrument to measure physical education teachers' attitudes toward stimulating HOTS in student. This study used a research and development design with the development stages consisting of a content validity test, ICC test, construct validity, reliability test and concuren validity. Based on these tests, it can be stated that 29 statement items have met the validity and reliability standards. Hence, the PE-SHOTS questionnaire instrument developed in this study is suitable